In vitro activity of A-56268 (TE-031), a new macrolide antibiotic, compared with that of erythromycin and other antimicrobial agents. - Floyd-Reising, S (1987)
A-56268 is a new macrolide antibiotic that resembles erythromycin in its spectrum of activity. A-56268 and erythromycin had identical activities against Streptococcus pyogenes, group B, C, and G streptococci, and viridans group streptococci. Erythromycin and A-56268 had similar activities against Staphylococcus aureus, coagulase-negative staphylococci, and group D enterococci. Like erythromycin, A-56268 was ineffective in inhibiting oxacillin-resistant S. aureus, oxacillin-resistant, coagulase-negative staphylococci, and penicillin-resistant viridans group streptococci. Haemophilus influenzae, Neisseria gonorrhoeae, and Legionella spp. were inhibited by A-56268 at concentrations similar to those of erythromycin.